Kritik Pasal 23 Ayat (1) UU No. 17 Tahun 2012 Terhadap Perlindungan Hukum dalam Regulasi Hak Anggota Koperasi Simpan Pinjam Dalam Pasal 15-116 Permenkop UKM No.8 Tahun 2023 - Aditya Cindi Pradana (Media Hukum Indonesia (MHI), 2026)
This study aims to explain the regulation of the rights of members of Savings and Loan Cooperatives as stipulated in Articles 15â€“16 of the Regulation of the Minister of Cooperatives and SMEs, and to examine the critique of Article 23 paragraph (1) of Law No. 17 of 2012 regarding legal protection in the regulation of the rights of Savings and Loan Cooperative members under Articles 15â€“16 of the Regulation of the Minister of Cooperatives and SMEs No. 8 of 2023. This research is qualitative in nature, using a library research design. The results of the study indicate that, first, Article 15 regulates the obligation to amend business licenses and service networks when there are changes to the name or office address of a cooperative through the government licensing system, implemented in accordance with prevailing laws and regulations. Article 16 guarantees exemption from fees for all risk-based licensing services for cooperative savings and loan businesses. Overall, these two articles ensure administrative smoothness in the operations of savings and loan cooperatives without excessive bureaucratic or financial burdens. These provisions support service continuity for members, although they do not explicitly mention internal mechanisms such as approval by the Membersâ€™ Meeting. Second, Article 15 of the Regulation of the Minister of Cooperatives and SMEs No. 8 of 2023 is not aligned because the phrase â€œmust be amended through the licensing systemâ€ in paragraph (1) ignores the exclusive authority of the Membersâ€™ Meeting in determining structural changes that affect savings and loan operations. Article 16 is also considered inconsistent, as the provision on licensing fee exemptions is not linked to approval by the Membersâ€™ Meeting regarding the use of business results or loan limits. Both articles do not demonstrate any alignment with Article 23 paragraph (1) of Law No. 17 of 2012, which explicitly emphasizes the authority of the Membersâ€™ Meeting.